INSECTICIDAL EFFICACY OF CYPERMETHRIN 25% PYRETHROID - Abdullaeva D. O; A. Ruzimurodov (International Engineering Journal For Research & Development, 2020)
The article provides information on the harm of synanthropic insects to human health. Drosophila Fll. The results of the study of the effect of the drug Cypermethrin 25% (k.e.) on the nutrition of the offspring are presented. In this case, a 0.07% aqueous emulsion of the drug was found to be 100% insecticidal.